Chemical profile and defensive function of the latex of Euphorbia peplus. (April 2017) - Hua, Juan; Liu, Yan; Xiao, Chao-Jiang; Jing, Shu-Xi; Luo, Shi-Hong; Li, Sheng-Hong
Abstract: Plant latex is an endogenous fluid secreted from highly specialized laticifer cells and has been suggested to act as a plant defense system. The chemical profile of the latex of Euphorbia peplus was investigated. A total of 13 terpenoids including two previously unknown diterpenoids, (2 S *, 3 S *, 4 R *, 5 R *, 6 R *, 8 R *, l1 R *, 13 S *, 14 S *, 15 R *, 16 R *)-5, 8, 15-triacetoxy-3-benzoyloxy-11, 16-dihydroxy-9-oxopepluane and (2 R *, 3 R *, 4 S *, 5 R *, 7 S *, 8 S *, 9 S *, l3 S *, 14 S *, 15 R *)-2, 5, 8, 9, 14-pentaacetoxy-3-benzoyloxy-15-hydroxy-7-isobutyroyloxyjatropha-6(17), 11 E -diene), ten known diterpenoids, and a known acyclic triterpene alcohol peplusol, were identified, using HPLC and UPLC-MS/MS analyses and through comparison with the authentic compounds isolated from the whole plant. The diterpenoids exhibited significant antifeedant activity against a generalist plant-feeding insect, the cotton bollworm ( Helicoverpa armigera ), with EC50 values ranging from 0.36 to 4.60 μg/cm 2 . In particular, (2 R *, 3 R *, 4 S *, 5 R *, 7 S *, 8 S *, 9 S *, l3 S *, 14 S *, 15 R *)-2, 5, 9, 14-tetraacetoxy-3-benzoyloxy-8, 15-dihydroxy-7-isobutyroyloxyjatropha-6(17), 11 E -diene and (2 R *, 3 R *, 4 S *, 5 R *, 7 S *, 8 S *, 9 S *, l3 S *, 14 S *, 15 R *)-2, 5, 14-triacetoxy-3-benzoyloxy-8, 15-dihydroxy-7-isobutyroyloxy-9-nicotinoyloxyjatropha-6(17), 11 E -diene had EC50 values of 0.36 and 0.43 μg/cm 2, respectively, which were approximately 7-fold more potent than commercial neem oil (EC50 = 2.62 μg/cm 2 ). In addition, the major peplusol showed obvious antifungal activity against three strains of agricultural phytopathogenic fungi, Rhizoctonia solani, Colletotrichum litchi and Fusarium oxysporum f. sp. niveum . The results indicated that terpenoids in the latex of E . peplus are rich and highly diversified, and might function as constitutive defense metabolites against insect herbivores and pathogens for the plant. Graphical abstract: Chemical profile of the latex of Euphorbia peplus was investigated. Thirteen structurally diversified terpenoids including two previously undescribed diterpenoids were identified. Antifeedant and antifungal activities of these terpenoids were observed, indicating that they might function as constitutive defense metabolites against insect herbivores and pathogens for the plant. Highlights: Chemical profile of the latex of Euphorbia peplus was investigated. 13 terpenoids including two previously undescribed diterpenoids were identified. The diterpenoids exhibited potential antifeedant activity. The acyclic triterpenoid peplusol showed antifungal activity. Latex terpenoids of Euphorbia peplus function as constitutive defense metabolites.